SOSIABILITAS PARA NETTER DI INDONESIA: KASKUSER REGIONAL YOGYAKARTA - Weni Arindawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2016)
AbstractThis is a study on the sociability of netters as reflected in the phenomenon of virtual community or online groups. This study attempts to investigate how the sociability of netters, KASKUS community of Yogyakarta Region, is shaped in cyberspace. As a result, this study is aimed at understanding and explaining the sociability built by the netters. Besides, this study is aimed at describing the communication, consolidation, and confirmation of the netters. And , it is also aimed at pointing out the dissimilarity or similarity of online and offline sociability. In virtual ethnographic research, theinteraction of virtual communities can actually be assessed based on its Computer-mediated Communication (CMC) practices. Therefore, observations are conducted by the researcher to explorethe experience and self-reflection of both the researcher herself and informants. As a consequence, this study can be classified into a qualitative research involving a combination of ethnographic observation, interviews, and group discussions. Key words: virtual community; sociability; CMC; KASKUS